Atypical giant proliferating cystic pilomatrixoma: A case review - Kerman Sekhon; Yvette Miller-Monthrope; Christian Murray; Michael Weinberg (SAGE Open Medical Case Reports)
Pilomatrixoma, or calcifying epithelioma of Malherbe, is a rare and benign tumour. Typical presentation of pilomatrixoma is solitary, firm lesions found in the head and neck regions. Pilomatrixoma are often misdiagnosed due to their clinical presentation, which is synonymous with other cutaneous pathology. The reported and true incidence of pilomatrixoma are 1% and 16%, respectively. Cystic pilomatrixoma is a unique variant that presents without the pathognomonic feature of a firm lesion. This study presents the case of a 52-year-old man with a post-auricular pilomatrixoma. It is erythematous, soft, mobile, and 4 cm in diameter. Its size categorizes the lesion as a giant pilomatrixoma. These pilomatrixoma pose a diagnostic challenge as they mimic malignant lesions. It was highly erythematous and mimicked Merkel cell carcinoma in on initial presentation. It was a sebum-filled lesion, which is quite atypical for pilomatrixoma. A previous study finds that only three cases of cystic pilomatrixoma have been reported in the literature previously. This case study presents the case of an atypical variant of a rare tumour. There is a paucity in the literature on cystic pilomatrixoma. Giant proliferating cystic pilomatrixoma has not previously been described in a case report in the literature, as to our knowledge. This study highlights the diversity in the clinical presentations of pilomatrixoma to improve our clinical sensitivity to pilomatrixoma.